“South-South” Learning Exchange for Client Capacity Enhancement - World Bank (World Bank, Washington, DC, 2012)
Client feedback surveys in Africa indicate that the Bank's performance requires strengthening with regard to (a) respect for local cultures, (b) adaptation of knowledge to the local context and (c) incorporation of local knowledge into development efforts. They would like to see greater involvement by beneficiaries and local project experts in project design to ensure that country conditions are better taken into account.